2021
DOI: 10.1111/jam.15120
|View full text |Cite
|
Sign up to set email alerts
|

A requirement for flow to enable the development of Ureaplasma parvum biofilms in vitro

Abstract: Aims: To use a flow-based method to establish, quantify and visualize biofilms of Ureaplasma parvum. Methods and Results: Absorbance readings of a U. parvum HPA5 culture were taken at 550 nm every 3 h for 30 h in order to establish a growth curve, with viability determined by the number of colour changing units (CCUs). Biofilms were established using the DTU flow-cell with a flow rate of 0Á01 ml min À1 and compared to the static control. Titres of bacteria were determined by CCU and biofilm biomass was quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The flow method was analyzed to evaluate the biofilm growth in Ureaplasma parvum, favoring the removal of toxic metabolites mediated by cell death. This is the first report on the quantification of the biofilm formed by Ureaplasma parvum, making it possible to establish a viable biofilm that will allow the evaluation of antimicrobial agents and a better understanding of the virulence associated with adhesion [11].…”
Section: Resultsmentioning
confidence: 99%
“…The flow method was analyzed to evaluate the biofilm growth in Ureaplasma parvum, favoring the removal of toxic metabolites mediated by cell death. This is the first report on the quantification of the biofilm formed by Ureaplasma parvum, making it possible to establish a viable biofilm that will allow the evaluation of antimicrobial agents and a better understanding of the virulence associated with adhesion [11].…”
Section: Resultsmentioning
confidence: 99%
“…The architecture of the biofilm produced by other mycoplasmas has already been studied; M. pneumoniae is able to form volcano-like structures [ 28 ], while M. pulmonis creates tower structures in vitro [ 29 ]. Images taken with a scanning electron microscope of the biofilm produced by Mg during another study [ 15 ] showed the presence of lichen-like structures, which are very similar to those created by M. fermentans [ 30 ] and Ureaplasma parvum [ 31 ]. In another study on Ms [ 16 ], both mushroom-like and tower-like structures were observed in the biofilm, even though the authors investigated the biofilm produced as soon as the culture broth was acidified.…”
Section: Discussionmentioning
confidence: 99%
“…Ureaplasma parvum is a member of the class of Mollicutes, frequently found in the urogenital ecosystem of asymptomatic “healthy” women as a commensal colonizer [ 24 ]. Mycoplasmas adhere to epithelial cells by means of individual surface-associated adhesins, such as multiple-banded antigens, and possesses the ability to form a biofilm [ 25 , 26 ]. Thus, we can speculate that a higher abundance of U. parvum in the urogenital tract could be a “protective factor”, preventing the subsequent adhesion and colonization of exogenous pathogens, including chlamydia.…”
Section: Discussionmentioning
confidence: 99%